Emerging Signaling Pathway in Arcuate Feeding-Related Neurons: Role of the Acbd7 - Lanfray, Damien; Richard, Denis (Frontiers in Neuroscience, 2017)
The understanding of the mechanisms whereby energy balance is regulated is essential to the unraveling of the pathophysiology of obesity. In the last three decades, focus was put on the metabolic role played by the hypothalamic neurons expressing proopiomelanocortin (POMC) and cocaine and amphetamine regulated transcript (CART) and the neurons co-localizing agouti-related peptide (AgRP), neuropeptide Y (NPY) and gamma-aminobutyric acid (GABA). These neurons are part of the leptin-melanocortin pathway, whose role is key in energy balance regulation. More recently, the metabolic involvement of further hypothalamic uncharacterized neuron populations has been suggested. In this review, we discuss the potential homeostatic implication of hypothalamic GABAergic neurons that produce Acyl-Coa-binding domain containing protein 7 (ACBD7), precursor of the nonadecaneuropeptide (NDN), which has recently been characterized as a potent anorexigenic neuropeptide capable of relaying the leptin anorectic/thermogenic effect via the melanocortin system.